Efektivitas Peran Caregiver Terhadap Penerapan Diet Hipertensi pada Lansia - Nouvi Nawa Syarifah; Dinasti Pudang Binoriang (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2026)
Hypertension is a crucial health problem in the elderly (aged ?60 years) in Indonesia, with a high prevalence of up to 69.5% in those aged ?75 years (Barus Sitorus, 2025). Control through a low-salt diet requires the role of family caregivers, because the elderly are often dependent due to limited independence and minimal formal education. To assess the effectiveness of hypertension education assistance to caregivers for implementing a diet in elderly people with hypertension. Descriptive case study on elderly (84 years old) and family caregiver in Dukuh Sonopakis Kidul, Bantul (October 15–November 12, 2025). Intervention 4 meetings (education definition, risks, complications, control, diet via posters; blood pressure checks). Results: Hypertension education assistance to caregivers has proven effective as evidenced by the caregiver's understanding of hypertension knowledge, statements by the elderly about reduced complaints such as dizziness and insomnia, and gradual improvement in blood pressure throughout the meeting sessions. Effective mentoring improves knowledge and dietary compliance in the elderly, demonstrating the crucial role of caregivers in implementing a hypertension diet for the elderly